THE PRESENCE OF THE GRIMM IN THE TALE OF THE THREE BROTHERS, BY J. K. ROWLING - Louzada Ferreira de Morais, Guilherme Augusto [UNESP]; Fernandes de Paula, Danytiele Cristina (Univ Estadual Mato Grosso Sul, 2020)
This paper compares two fairy tales of different nationalities: The Wishing-Table, the Gold-Ass, and the Cudgel in the Sack, by the German brothers Jacob and Wilhelm Grimm, and The tale of the three brothers, by J. K. Rowling, with the aim of highlighting that Rowling's text very much resembles the Grimm's narrative. In addition to verifying the intertextual relations between both texts, it is sought to demonstrate that there is a unifying element between them: the number three. The two stories are analyzed through studies on the symbology of number three, and the recurrence of the common denominator is demonstrated, as in the supply of three magical objects, which have a decisive role in the development of the narrative of both stories.
Keywords: fairy tale; number three; brothers Grimm; J. K. Rowling